INDIVIDUALITY DYNAMIC ANALYSIS OF THE PROTAGONIST’S CHARACTER IN THOMAS HARDY’S NOVEL TESS OF THE D’URBERVILLES - Safnidar Siahaan (CAHAYA PENDIDIKAN, 2016)
Tess of the D’Urbervilles is a novel written by Hardy that describes Tess as the victim of men who fall in love with her. The protagonist’s character in this novel will be analysed based on psychoanalysis theory especially about the dynamic of individuality explaining about the power urging behind the human’s action.  The result is expected to give the reader a description and understanding Tess character based on psychoanalysis theory especially based on individuality dynamic part. Keywords: drive, sexuality, aggression, anxiety